Housing expenditures and income inequality - Christian Dustmann; Bernd Fitzenberger; Markus Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
In this paper, we show that, in terms of real disposable income, changes in housing expenditures dramatically exacerbate the trend of income inequality that has risen sharply in Germany since the mid-1990s. More specifically, whereas the 50/10 ratio of net household income increasesby 22 percentage points (pp) between 1993 and 2013, it increases by 62 pp for income net of housing expenditures. At the same time, the income share of housing expenditures rises disproportionally for the bottom income quintile and falls for the top quintile. Factors contributing to these trends include a decline in the relative costs of homeownership versus renting, changes in household structure, and residential mobility toward larger cities. Younger cohorts spend more on housing and save less than older cohorts did at the same age, with possibly negative consequences for wealth accumulation, particularly for those at the bottom of the income distribution.
Keywords: D31; R21; 330; income inequality; housing expenditures